Assisted Reproductive Technology Regulations in Indonesia: A Systematic Review from the Perspectives of Health Law and Islamic Fiqh in the Archipelago - Gusasih, Bahar Sangkur; Prasetyawati, Faradilla Savitri; Fikri, Ahmad Ma’mun (Proceedings: International Seminar On Educational Studies, 2025)
Assisted Reproductive Technology (ART) raises complex legal, ethical, and religious implications in Indonesia. This study aims to analyze the synchronization between positive health regulations in Indonesia and the Islamic Fiqh perspective in the archipelago regarding ART practices. This study uses a systematic literature review method of secondary data sources, including scientific literature, the latest legislation (Law No. 17 of 2023; Government Regulation No. 28 of 2024; Minister of Health Regulation No. 2 of 2025), and the Indonesian Ulema Council (MUI) fatwa. The collected data were analyzed using thematic synthesis. The main results show a strong synchronization between positive law and Fiqh. The new regulations explicitly prohibit the practice of gamete donation (sperm/ovum/embryo) and surrogacy, which is fully in line with the MUI Fatwa based on the principle of protecting lineage (hifdz an-nasl). A key finding is the inclusion of an explicit clause in Law 17/2023 and Government Regulation 28/2024 that the implementation of ART “does not conflict with religious norms,” which proves the absorption of Fiqh values into state law. In conclusion, TRB regulations in Indonesia are not secular, but actively integrate the values of Tamadun Islam Nusantara to strengthen the social order and protect lineage. This review also identifies ‘gray areas’ such as sex selection, which require further regulatory review.